Asymmetric trading costs and ancient Greek cities - Chen, Y; Ioannides, YM; Rauch, F (University of Oxford, 2022)
Asymmetric transport costs arise when shipping times from point i to point j differ from shipping from point j to i. We show that such asymmetric transport costs predict distinct patterns of location in a class of models using Dixit-Stiglitz preferences. We then study factors affecting the location of cities in ancient Hellas. Prevailing winds create an environment of asymmetric trade costs in ancient Greece. We show that predictions of these models are consistent with the location of ancient cities.